2020
DOI: 10.1111/coa.13640
|View full text |Cite
|
Sign up to set email alerts
|

HPV genotype is a prognosticator for recurrence of respiratory papillomatosis in children

Abstract: Recurrent respiratory papillomatosis (RRP) is a rare condition characterised by exophytic proliferative lesions (papillomas) in the airway, mainly at the larynx, caused by human papillomavirus (HPV) infection. The symptoms may vary from hoarseness to respiratory distress, and the disease may present a devastating impact on the quality of life of affected patients due to the high number of recurrences, often requiring multiple surgeries, or even tracheostomy. 1 The prevalence of RRP is in decline with the intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
(45 reference statements)
2
5
0
Order By: Relevance
“…The authors identified three different HPV6 subtypes: HPV6a, HPV6b, and HPV6vc, with the latter being the most common. HPV6 subtype or viral load/HPV mRNA expression levels were not associated with the clinical parameters (age, sex, tumor location, Derkay score) [ 73 ], as also recently confirmed by two other studies [ 10 , 74 ]. Sichero L et al (2021) found no association between any particular HPV11 variant and clinic-pathological features among the 79 RRP patients studied [ 74 ].…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)supporting
confidence: 72%
See 3 more Smart Citations
“…The authors identified three different HPV6 subtypes: HPV6a, HPV6b, and HPV6vc, with the latter being the most common. HPV6 subtype or viral load/HPV mRNA expression levels were not associated with the clinical parameters (age, sex, tumor location, Derkay score) [ 73 ], as also recently confirmed by two other studies [ 10 , 74 ]. Sichero L et al (2021) found no association between any particular HPV11 variant and clinic-pathological features among the 79 RRP patients studied [ 74 ].…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)supporting
confidence: 72%
“…The outcomes of RRP are variable among individual patients, and several studies have focused on the risk factors associated with a more aggressive outcome. Most studies agree that a younger age at onset of JO-RRP is an important independent predictor of disease severity [ 10 , 15 , 16 , 64 ]. Age at onset was the only significant risk factor for aggressive disease in JO-RRP, whereas in adults, both HPV11 and observation time ≥10 years were significant [ 64 ].…”
Section: Laryngeal Squamous Cell Papillomas (Rrp)mentioning
confidence: 95%
See 2 more Smart Citations
“…Numerous case studies of HPV11+ RRP patients have been reported that detail the fatal progression of the disease [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Similarly, analysis of retrospective cohorts has suggested that HPV11+ disease is associated with worse outcomes [ 19 , 20 , 21 , 22 , 23 , 24 ]. However, others have countered these findings [ 25 , 26 , 27 , 28 ] or concluded that an early age of onset, and not the HPV strain, predicts disease severity [ 29 , 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%